2022
DOI: 10.1302/2633-1462.36.bjo-2022-0043.r1
|View full text |Cite
|
Sign up to set email alerts
|

High rate of tibial debonding and failure in a popular knee replacement

Abstract: Aims Total knee arthroplasty (TKA) is a common and safe orthopaedic procedure. Zimmer Biomet's NexGen is the second most popular brand of implant used in the UK. The primary cause of revision after the first year is aseptic loosening. We present our experience of using this implant, with significant concerns around its performance with regards early aseptic loosening of the tibial component. Methods A retrospective, single-surgeon review was carried out of all of the NexGen Legacy Posterior Stabilized (LPS) TK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…As stated above, it can be assumed that the majority of aseptic loosening cases are not related to mechanical issues such as malpositioning or cement debonding as those would likely manifest early. (16)(17)(18)(19)(20)(21) Thus, in the current study of mid-to long-term failures, early stage osteolysis caused by wear debris or other foreign bodies (e.g. cement debris, corrosion products, etc.)…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…As stated above, it can be assumed that the majority of aseptic loosening cases are not related to mechanical issues such as malpositioning or cement debonding as those would likely manifest early. (16)(17)(18)(19)(20)(21) Thus, in the current study of mid-to long-term failures, early stage osteolysis caused by wear debris or other foreign bodies (e.g. cement debris, corrosion products, etc.)…”
Section: Discussionmentioning
confidence: 94%
“…Instability is commonly attributed to malpositioning, cement debonding, or other mechanical issues, which would likely manifest within the first 5 years after primary surgery. (16)(17)(18)(19)(20)(21) Therefore, it is plausible that instability in the mid-to long-term frequently may occur secondary to delamination. Delamination, which is the result of surface fatigue wear under combined rolling and sliding motion in the knee, has been a prominent problem in TKA with tibial inserts made from historic PE leading to early failures.…”
Section: Discussionmentioning
confidence: 99%
“…Concerns over the early aseptic failure of modern TKAs is not an issue unique to the Attune ® prostheses. Keohane et al recently reported an exceptionally high rate of aseptic loosening in the NexGen ® implant design in their series which has subsequently been recalled by the manufacturer [ 18 ].…”
Section: Discussionmentioning
confidence: 99%